A methodology for characterization and analysis of plant functional composition in grassland‐based farms. (14th September 2012) - Duru, M.; Hossard, L.; Martin, G.; Theau, J. P.
Abstract Understanding the relationships between farmers' land‐use and management decisions, and plant diversity is a challenge. It requires characterization of plant diversity within and between fields and investigation of land‐use allocation to fields. To analyse how grassland functional composition [mean plant trait and functional diversity index (FD)] varies according to scale (field, land‐use type: cutting, grazing, farm), grasslands were characterized according to leaf dry‐matter content (leaf DM) and FD computed from leaf DM values. A leaf DM‐αFD framework was used to analyse how leaf DM‐based plant strategies were distributed at land‐use type and farm scales (βFD). The study was conducted on eight dairy and beef farms (169 grasslands) differing in their stocking rate. At field and land‐use type scales, leaf DM was significantly decreased and increased with N fertilizer rate and field elevation respectively. It was significantly higher for grazing than for cutting. At the farm scale, the main differences between farms resulted from differences in plant strategy distribution between land‐use types within a farm and among farms for a given land‐use type in relation to management intensity. Farms that contributed the most to αFD had the highest stocking rate, and those which had the most contrasting grasslands for management intensity had the highest βFD. Management practices need to be examined at a land‐use type scale for evaluating the within‐ and between‐field plant functional compositions. By contrast, the value of the analysis was reduced if data were collected and averaged at the farm scale.